Regional differentiation of direct support for farmers in Poland as exemplified by selected regions - Sadłowski, Adrian (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
The objective of this study was to measure the dispersion of the unit level of support, paid under the direct payment scheme, among voivodeships with a similar average agricultural holding size, and to identify the reasons for this dispersion. It begins with a description of the shape of the direct payments scheme in Poland. The paper further presents and analyses the results of the measurement of dispersion of support as part of the direct payment scheme between voivodeships with no significant differences in the sizes of agricultural holdings. It has been shown that this dispersion is a result of the differences in the structure of support absorbed by farmers in individual regions. The measurement of the support level is the average aid amount per unit of agricultural area and the average aid amount per one beneficiary. The source material used in this paper was the data from the Polish paying agency responsible for direct payments made to farmers, i.e. the Agency for Restructuring and Modernisation of Agriculture. The reference period of the study is 2018. As three voivodeships with the most similar average farm size were selected, the study covered Łódzkie, Śląskie and Lubelskie Voivodeships. The analysis was performed with the use of descriptive statistics methods. The data was visualised with the use of pie and bar charts, and a choropleth map. It was found that the instrument with a particularly strong potential for the impact on support level in absolute terms (per one holding) and relative terms (per 1 hectare of agricultural land in a holding) is the so called voluntary coupled support. With this instrument, European Union Member States can adjust the distribution of funds between individual regions, reducing the strength of a relationship between the volume of support absorbed by individual regions and their abundance in agricultural land. The intention of such actions may be to compensate for social inequalities or to stimulate growth in peripheral areas.

Celem opracowania było rozpoznanie zróżnicowania jednostkowego poziomu wsparcia, wypłacanego w ramach systemu płatności bezpośrednich, między województwami o zbliżonej średniej wielkości gospodarstwa oraz identyfikacja przyczyn tego zróżnicowania. W pierwszej kolejności przybliżono kształt systemu wsparcia bezpośredniego w Polsce. Następnie przedstawiono i omówiono wyniki pomiaru dyspersji średniego poziomu wsparcia w ramach systemu płatności bezpośrednich, występującej między województwami nieróżniącymi się istotnie średnią wielkością gospodarstwa. Wykazano, że zróżnicowanie to jest następstwem różnic w strukturze pomocy zaabsorbowanej przez rolników z poszczególnych regionów. Za miernik poziomu wsparcia przyjęto średnią kwotę pomocy przypadającą na jednostkę powierzchni użytków rolnych oraz średnią kwotę pomocy przypadającą na beneficjenta. Jako materiał źródłowy wykorzystano dane polskiej agencji płatniczej odpowiedzialnej za wypłatę płatności bezpośrednich na rzecz rolników, którą jest Agencja Restrukturyzacji i Modernizacji Rolnictwa. Zakres czasowy badań to 2018 r. Jako, że do porównań wybrano trzy województwa o najbardziej zbliżonej średniej powierzchni gospodarstwa, zakres przestrzenny badań obejmuje województwo łódzkie, województwo śląskie i województwo lubelskie. Analizę przeprowadzono z wykorzystaniem metod opisu statystycznego. Do wizualizacji danych zastosowano wykresy udziałowe (kołowo-kolumnowe) i kartogram. Stwierdzono, że instrumentem o szczególnie silnym potencjale oddziaływania na poziom wsparcia w ujęciu absolutnym (na gospodarstwo) i względnym (w przeliczeniu na 1 ha użytków rolnych gospodarstwa) jest tzw. dobrowolne wsparcie związane z produkcją. Za pomocą tego instrumentu państwa członkowskie Unii Europejskiej mogą w znacznym stopniu korygować rozdział środków między poszczególne regiony, zmniejszając siłę związku wielkości pomocy absorbowanej przez poszczególne regiony z ich zasobnością w użytki rolne. Intencją takich działań może być kompensowanie nierówności społecznych czy stymulowanie wzrostu na obszarach peryferyjnych.
Keywords: Common Agricultural Policy; direct payments; average level of support; Wspólna Polityka Rolna; płatności bezpośrednie; średni poziom wsparcia